The Theatre of the Oppressed like modern way for prevention emotional burnout of volunteers in non-governmental organizations - Tkachenko, Давид (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to the Theatre of the Oppressed like modern way for prevention emotional burnout of volunteers in non-governmental organizations.